KIRAAT AÇISINDAN BEGAVÎ TEFSİRİ - SAYLAN, NESRİŞAH (Fırat Üniveristesi, 2015)
Bu çalışma, V/XII. yüzyıl âlimlerinden Begavî'nin Me'âlimu't-Tenzîl adlı tefsirinde esas aldığı kıraat anlayışının tayinini ve kıraatleri kullanma keyfiyetinin tespitini amaçlamaktadır. Begavî'nin tefsirinde naklettiği kıraatlerin tefsir ve Arap diliyle olan irtibatı temelinde, kıraat-lehçe, sarf-nahiv ve kıraat-tefsir ilişkisinin incelendiği araştırmada, öncelikle, kıraat ilmi ve tarihi hakkında özet bilgi verilmiş, akabinde de Begavî'nin hayatı ve ilmî şahsiyeti üzerinde durulmuştur. Ana izleği itibariyle ise çalışmada Begavî'nin kıraat ilmindeki yeri, kıraatteki kaynakları, kıraatleri nakil yöntemi ve kıraatleri işleyiş tarzı üzerinde durulmuş, bunun da ötesinde Begavî'nin mana takdirlerinde kıraat farklarına ne gibi bir rol atfettiği, başta filolojik ve fıkhî yorum olmak üzere tefsir ve te'vil etkinliğinde kıraatleri nasıl kullandığı diğer tefsir ve kıraat kaynaklarıyla mukayeseli olarak incelenmiştir. Anahtar Kelimeler: Begavî, Tefsir, Kıraat, Kıraat-i Aşere, Kârî, Sahih, Şâz, Mushaf.

This study aims assignment understanding of the recitation and the determination of the using arbitrariness of recitation in the 5th and 12th century scholar Begavî's interpretation called Mealimut Tenzil. In he study in which the connection of the recitation of Begavî's interpretation he carried forward with Arabic, the residation-dialect, supplies-nahiv, recitation-interpretation collaboration, we especially gave information about the rcitation science and its history and then we stood on the issue of Begavî's life and his scientific personality. As the min theme of the study we stood on Begavî's place in science of recitation, the sources of the recitation, his method to transfer the recitations and his mode of recitations. Beyond that we studied how Bergavi attributed to the recitation difference in appreciation meaning and how he used the recitation especially the philological and jurisprudence comment, interpretation and interpretation efficietly. This has been compared with the interpretation and recitation sources comparatively. Key Words: Begavî, İnterpretation, Recitation, Reading ten of the recitation sciences, Reader, Reality, Shadhdh, al-Musha
Begavî's interpretation in view of recitation
Keywords: Din